Analysis of Antioxidant Content in Pollen and Honey Produced by Bees Trigona spp At Several Locations In South Sulawesi - Nur Ramaliani Samsul; Eva Johannes; Syahribulan Syahribulan (International Journal of Applied Biology, 2022)
Trigona bees spp has a potential utilization of this bee is not inferior to Apis sp. The use of stingless honey bees in South Sulawesi has been carried out in several districts such as Selayar, Maros and Gowa. Trigona bees spp produce pollen and honey which contain antioxidants, antioxidants are compounds that can neutralize or destroy free radicals, so as to prevent various diseases. This research was conducted to analyze the antioxidant content of pollen and honey produced by the three districts and compare them with each other. Antioxidant levels was carried out using the DPPH method (2,2-diphenyl-1-picrylhydrazyl) with vitamin C was used as positive control. The results of the determinining the wavelength used using a UV Vis spectrophotometer obtained a wavelength of 513 nm used with the test results of antioxidant levels of Pollen extract from the Selayar location were 1666.33 µg/g, Pollen Maros 431.70 µg/g and Pollen Gowa 259.56 µg/g and the antioxidant content of honey from Selayar was 43.62 µg/g, Maros honey 28.08 µg/g and Gowa honey 31.80 µg/g. Pollen and Honey from Selayar had the highest antioxidant levels from the three locations.